Zastosowanie wybranych aplikacji internetowych w dziennikarstwie danych – analiza porównawcza - Król, Karol (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
Media convergence and multimediality of message brought about a situation where journalists and editors of the content posted on the Internet are more and more frequently required to acquire the skills which have never been necessary for them before. It often forces them to become acquainted with professional software and information technology. On the other hand, availability of different databases and Internet applications provides journalists with possibilities of gathering, processing and visualization of data unheard of to date. The objective of the paper was a comparative analysis of selected Web applications generating interactive maps, data charts and diagrams, that may be useful in journalist’s everyday work, in the browser in an automatic way. The conducted research allows concluding that the tested applications may be applied in Internet, citizen or data journalism, that is wherever the concise and attractive form of data visualization is of primary importance.